The supraclavicular nerve. Issue 6 (14th April 2022) - Seror, Paul
Abstract: Introduction/Aims: The aim of this study was to describe a new method for studying the supraclavicular nerve (SCN) conduction and to report four cases with SCN lesions. Methods: The SCN was antidromically recorded with a pair of self‐adhesive electrodes located in the middle of the clavicle. Stimulation (<5 mA) was delivered 7 cm proximally with a bar electrode. To facilitate recording, it was explained to the participant that they would feel a very faint electrical sensation locally and an electrical tingle upward (ear) or downward (shoulder/clavicle). Each participant was asked to say when the tingling moved downward. Results: In normal subjects, median values were 16 μV (range: 9–33) for sensory nerve action potential (SNAP) amplitude; 1.2 ms (range: 1–1.5) for onset latency; and 1.25 (range: 1–1.7) for side‐to‐side amplitude ratio. In the four patients, the SCN SNAP was absent on the pathological side and normal on the healthy side. All four patients complained of unilateral neuropathic hypoesthesia on the anterior aspect of the neck, chest, and shoulder that occurred after radical neck surgery for thyroid or larynx cancer (x3) and first rib resection (x1). Discussion: A comparison with previous reports shows that this simple method provides similar or highest SNAP amplitudes. SCN lesions are rare, and rarely referred for electrodiagnosis, and often overlooked. However, the SCN conduction study, which causes very slight inconvenience (low‐intensity stimulation), allows a better understanding of the origin of the complaints and permits the patient to benefit of more suitable treatment.